MO490SYMPTOM BURDEN AND ITS IMPACT ON QUALITY OF LIFE IN PATIENTS WITH MODERATE TO ADVANCED CKD. (29th May 2021) - Speyer, Elodie; Tu, Charlotte; Zee, Jarcy; Sesso, Ricardo; Lopes, Antonio; Hoshino, Junichi; Ayav, Carole; Pisoni, Ronald; Pecoits-Filho, Roberto; Stengel, Benedicte
Abstract: Background and Aims: It is generally considered that the early stages of CKD are asymptomatic, and that CKD becomes apparent once kidney function is significantly impaired, but large-scale studies in real-world non-dialysis CKD patients under nephrology care are still scarce. We evaluated symptom burden and its impact on quality of life in patients with moderate to advanced CKD. Method: 4423 patients with CKD Stage 3 to 5 from Brazil (N=548), France (N=2691), and the US (N=1184) enrolled in the Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDopps) from 2013-2019 completed the Kidney Disease Quality of Life (KDQOL) questionnaire at baseline to assess how much they were bothered by 13 symptoms. Response options ranged from "not at all" to "extremely" bothered. From these Symptoms/Problems of Kidney Disease items, a score was calculated, ranged from 0 to 100, and analyzed in 3 categories: low (≥90), intermediate (66-90), or high symptom burden (<66). Poisson regressions were used to estimate prevalence ratios for each symptom and to study associations between CKD stage and a high symptom burden before and after adjusting for demographics and major comorbidities. Multiple linear regression accounting for clustering at the clinic level was used to examine associations between high symptom burden and physical and mental component summary (PCS and MCS, respectively) scores, with lower scores indicating poorer quality of life. Results: Patients (mean age 68±13 years, 40% women, mean eGFR at baseline 30.4±12.2 mL/min/1.73m²) were very much to extremely bothered by a number of symptoms, the prevalence of three of which - washed out or drained, nausea or upset stomach, and lack of appetite – significantly increased in more advanced CKD stages before and after adjusting for confounders (Figure ). Nearly one in four patients reported a high symptom burden, which was more prevalent in women, those with obesity, anemia, or albumin<3.5 g/dL; it was also more common in France than in the US and Brazil. In adjusted models, as compared to patients with low symptom burden, those with high symptom burden had a worse quality of life with PCS and MCS scores 14.6 (95% confidence interval [95% CI], 15.7 to 13.5) and 7.2 (95% CI, 8.3 to 6.1) points lower, respectively. Conclusion: Our findings demonstrate a high symptom burden even in nondialysis CKD stages 3-5 with a substantial impact on physical and mental health-related quality of life. Several symptoms, particularly fatigue, and gastrointestinal symptoms, appeared to worsen with increasing CKD stage, independent of patient comorbidities.